2015
DOI: 10.1186/s12879-015-1238-8
|View full text |Cite
|
Sign up to set email alerts
|

Merozoite surface protein-1 genetic diversity in Plasmodium malariae and Plasmodium brasilianum from Brazil

Abstract: BackgroundThe merozoite surface protein 1 (MSP1) gene encodes the major surface antigen of invasive forms of the Plasmodium erythrocytic stages and is considered a candidate vaccine antigen against malaria. Due to its polymorphisms, MSP1 is also useful for strain discrimination and consists of a good genetic marker. Sequence diversity in MSP1 has been analyzed in field isolates of three human parasites: P. falciparum, P. vivax, and P. ovale. However, the extent of variation in another human parasite, P. malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…This variation could be attributed to positive selection, frequent recombination, and gene flow among the parasites, as follows. First, compared with msp 1, dhfr , and dhps of P. malariae ( 20 22 ), the csp gene revealed a remarkably higher level of sequence diversity. It is possible that selection of csp genetic variants may confer immunogenic advantages to the pathogen during host invasion ( 28 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation could be attributed to positive selection, frequent recombination, and gene flow among the parasites, as follows. First, compared with msp 1, dhfr , and dhps of P. malariae ( 20 22 ), the csp gene revealed a remarkably higher level of sequence diversity. It is possible that selection of csp genetic variants may confer immunogenic advantages to the pathogen during host invasion ( 28 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of genetic variation among isolates from these geographic areas is still lacking. One study indicated a remarkably low level of sequence diversity at the msp 1 locus in P. malariae from Brazil ( 20 ). Similarly, the lack of variation at the dhfr and dhps loci has been shown for P. malariae from Asia and the western Pacific region ( 21 , 22 ).…”
mentioning
confidence: 99%
“…P. falciparum and P. vivax MSP - 1 genes display extensive genetic diversity, which is often used as a molecular marker for population studies. To date, limited studies on PmMSP - 1 among Brazilian isolates and PocMSP - 1 on Thai isolates detected low-level sequence diversity with most of variations located at interspecies variable domains of this gene [46, 48]. Phylogenetic analysis of PmMSP - 1 using the maximum likelihood method placed the China–Myanmar border isolates separated from the Brazilian isolates, indicating divergent parasite populations.…”
Section: Discussionmentioning
confidence: 99%
“…These include the cytochrome b ( cytb ), cytochrome oxidase subunit 1 ( cox1 ) and glyceraldehyde - 3 - phosphate ( g3p ) genes of P. ovale spp., dihydropoteroate synthase ( dhps ) of P. malariae [43], dihydrofolate reductase ( dhfr ) and MSP - 1 genes in both species [4446]. Amplified fragments of DNA were purified, and sequenced directly or cloned into pMD18-T vector (Takara) for sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that a new world primate infective 160 species termed P. brasilianum is identical to P. malariae 21 . To investigate this further using the new genome assemblies, we aligned the P. brasilianum merozoite surface protein 1 (MSP1) 22 and ribosomal rRNA 21 genes to both the P. malariae and P. malariae-like orthologous genes, showing that P. brasilianum is identical to P. malariae, but that P. malariae-like is indeed very different (Supplementary Figure 165 2b).…”
mentioning
confidence: 99%